Effects of radiation on natural convection flow around a sphere with uniform surface heat flux - Akhter, Tahmina; Alim, MA (Journal of Mechanical Engineering, 2009)
The effects of radiation on natural convection flow around a sphere with uniform surface heat flux have been investigated in this paper. We have considered here a sphere with uniform surface heat flux immersed in a viscous incompressible optically thick fluid. The governing equations are first transformed into non-dimensional form and the resulting nonlinear systems of partial differential equations are then solved numerically using Finite-difference method with Keller-box scheme. We have focused our attention on the evolution of the shear stress in terms of local skin friction coefficient and the rate of heat transfer in terms of local Nusselt number. Also, velocity as well as temperature profiles are shown graphically for some selected values of radiation parameter (Rd), surface temperature parameter (D) and Prandtl number (Pr). Keywords: Thermal radiation, Prandtl number, natural convection, uniform surface heat flux. doi:10.3329/jme.v39i1.1834 Journal of Mechanical Engineering, vol. ME39, No. 1, June 2008 50-56